2017
DOI: 10.2147/bctt.s125745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <em>CYP2D6 </em>and <em>CYP3A5 </em>polymorphisms on tamoxifen and its metabolites in Thai breast cancer patients

Abstract: PurposeThis study aimed to determine the effects of CYP2D6 and CYP3A5 polymorphisms on the levels of tamoxifen (TAM) and its metabolites in the plasma of breast cancer patients. The protocol was designed to test the associations between CYP2D6, CYP3A5 genotypes and phenotypes (extensive metabolizer [EM], intermediate metabolizer [IM] and poor metabolizer [PM]) and TAM, N-desmethyl tamoxifen (NDMT), endoxifen (END) and 4-hydroxytamoxifen (4OHT) concentrations.Patients and methodsOne hundred and thirty-four Thai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…CYP3A5 *3 (rs776746) is a loss of function allele that is more common in African Americans (MAF = 0.13) than Caucasians (MAF = 0.01) [ 115 ]. Clinical studies have not reported any effect of CYP3A5 *3 on endoxifen levels [ 84 , 90 , 112 , 113 , 115 , 116 , 117 ], even in large studies that conducted subgroup analyses stratified by CYP2D6 and CYP2C9/19 phenotype [ 73 ].…”
Section: Contribution Of Other Enzymes To Tamoxifen Metabolite Conmentioning
confidence: 99%
“…CYP3A5 *3 (rs776746) is a loss of function allele that is more common in African Americans (MAF = 0.13) than Caucasians (MAF = 0.01) [ 115 ]. Clinical studies have not reported any effect of CYP3A5 *3 on endoxifen levels [ 84 , 90 , 112 , 113 , 115 , 116 , 117 ], even in large studies that conducted subgroup analyses stratified by CYP2D6 and CYP2C9/19 phenotype [ 73 ].…”
Section: Contribution Of Other Enzymes To Tamoxifen Metabolite Conmentioning
confidence: 99%
“…Confirming with previous studies CYP2C19*2 was associated with better efficacy of tamoxifen. CYP3A5 and CYP2C19 plays a minor role compared to CYP2D6 enzyme [69][70][71][72][73][74]. Therefore, researchers concluded there is an association between CYP genotypes and clinical pathology of breast cancer.…”
Section: Tamoxifen Resistance and Its Clinical Implicationmentioning
confidence: 99%
“…PMs due to CYP2D6 *5/*4 and *4/*5 genotypes have been previously reported to be associated with low and subtherapeutic levels of ENDO 47 and IM genotypes, such as CYP2D6*10 , have also been shown to be associated with low and sometimes subtherapeutic levels of ENDO. 46 , 47 These observations have led to CYP2D6 genotype dose escalation studies in Asians 37 and mixed populations 38 that have demonstrated that increasing the dose of TAM can raise ENDO to therapeutic levels. Our finding that patients carrying CYP2D6*17 and CYP2D6*29 diplotypes have ENDO concentrations below the therapeutic range implies that such patients might benefit from dose adjustments, as has been done for patients carrying the CYP2D6*10 in Asian populations 37 and in patients with diplotypes predictive of IMs in other populations.…”
Section: Discussionmentioning
confidence: 98%
“…The PM and IM genotypes were expected to have lower ENDO due to effects on the NDM to ENDO pathway catalyzed by CYP2D6. PMs due to CYP2D6 *5/*4 and *4/*5 genotypes have been previously reported to be associated with low and subtherapeutic levels of ENDO 47 and IM genotypes, such as CYP2D6*10 , have also been shown to be associated with low and sometimes subtherapeutic levels of ENDO 46,47 . These observations have led to CYP2D6 genotype dose escalation studies in Asians 37 and mixed populations 38 that have demonstrated that increasing the dose of TAM can raise ENDO to therapeutic levels.…”
Section: Discussionmentioning
confidence: 99%